Bending Vibrational Levels in the Electronic Spectra of Small Radicals. Issue 4 (4th January 2018) - Hsu, Yen‐Chu
Abstract : The role played by bending vibrations in the spectroscopy of small carbon‐containing radicals is illustrated by the patterns and effects shown by C3, CCH, and C3 Ar. Because of the large change in the bending frequency between the X ˜ 1 Σ + g and A ˜ 1 Πu states of C3, the A ˜ 1 Πu state provides one of the best known examples of the coupling of electronic and vibrational motion in linear molecules (the Renner–Teller effect). The X ˜ 2 Σ + and A ˜ 2 Π states of CCH provide a classic instance of vibronic coupling between two close‐lying electronic states, which leads very rapidly to a chaotic pattern of mixed‐state vibrational energy levels, which can only be understood by extensive high‐quality ab initio calculations. C3 Ar is an approximately T‐shaped molecule with no less than four large‐amplitude vibrations. Its A ˜ state provides a beautiful example of what happens to the angular momentum of a Π state of C3 when the symmetry is lowered by complex formation. Abstract : Jet‐cooled laser‐induced fluorescence spectrum of the A ˜ 1 Πu – X ˜ 1 Σ + g system of C3 in the frequency range 29 165–29 222 cm −1 . The 0 12 + 0 and 0 22 − 0 levels are among the highest pure bending levels of the system that have been observed. Also shown are bands going to a "mixed" Σ + u level at 29 209 cm –1 and the perturbed 2 6 + 0, Πu level.